Biodiversity of Bivalvia Tridacnidae in Marine Conservation Area : Lesson Learned from Abang Island, Kepulauan Riau Province-Indonesia - Ramses Ramses; Fauziah Syamsi; Thamrin Thamrin; Nofrizal Nofrizal; Hamdayani Hamdayani; Tengku Said Razai; Rika Kurniawan (Riau University, 2020)
Kima (local name) is known as a giant clam of a group of bivalve mollusca belonging to the Tridacnidae family that live in coral ecosystems zhich are considered as endangered species (CITES: Appendix II). This study aims to determine the biodiversity and ecological index of Tridacna in Abang Island waters, as well as determine the status of its presence in this area. A field survey was conducted on the type, number and distribution of tridacnae at each location by SCUBA equipment dive using the sweept area method on the transect lines. The transect wasplotted at 2-5 m in depth parallel to the shoreline at each observation station with covering observation area as far as 2.5 meters both on the left and 2 right side of the observers. The results showed 5 species of Kima with a total of 75 individuals, namely Tridacna maxima, T. Squamosa, T. crocea, T.derasa and H. hipppus. The densitywas maximal for T.maxima 0.014 individu/M2 folowing by T.squamosa (0.009/M2), T.crocea (0.006/M2), T.derasa (0.003/M2), H.hipppus (0.001/M2). While the relative density were T.maxima (44%), T.squamosa (26.7%), T.crocea (18.7%), T.derasa (8.0%), and H.hipppus (2.7%). The diversity index (H ') was 1.33 with representing a medium diversity category, dominance index (D) equal to 0.70 and Uniformity (E') equal to 0.82. T. maxima, T. squamosal, and T. crocea were found abundantly in the study area while T.derasa and H. hippopus were hard to find and T. gigaswasabsences presumably due to local extinction and functional extinction. Protectionof Tridacna in natural habitats is a must to maintain the ecological function and sustainability of Tridacn awith strict and controlled management.